1995
DOI: 10.1111/j.1432-1033.1995.tb20803.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Fast, Slow and Cardiac Muscle Tropomyosins from Salmonid Fish

Abstract: Tropomyosin (TM) has been isolated from the cardiac muscle, and fast and slow trunk (myotomal) muscles of the mature salmonid fish Atlantic salmon (SuZmo suZur) and rainbow trout (Sulmo guirdneri). When examined electrophoretically, isoforms of TM were detected which were specific, and exclusive, to each type of muscle. Cardiac and fast muscles contained single and distinct isoforms, while slow muscle contained two distinct isoforms, closely related in terms of apparent M, and PI. There was no detectable diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 65 publications
3
60
0
1
Order By: Relevance
“…Tropomyosins were prepared from adult fish as described in Heeley et al (1995). Atlantic salmon (Salmo salar), Arctic char (Salvelinus alpinus) and rainbow trout, (Salmo gairdneri) were used as sources of fast myotomal muscle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tropomyosins were prepared from adult fish as described in Heeley et al (1995). Atlantic salmon (Salmo salar), Arctic char (Salvelinus alpinus) and rainbow trout, (Salmo gairdneri) were used as sources of fast myotomal muscle.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work (Heeley and Hong, 1994;Heeley et al, 1995) has demonstrated that the major striated muscles of mature Atlantic salmon, and species of trout, possess a simple content of tropomyosin (TM), both in terms of the number of major isoforms which are present and their tissue distribution. The specific details arising from these studies were that heart and fast contracting myotomal (trunk) muscle each contain a single non-identical isoform while slow contracting myotomal muscle contains two, closely related, isoforms which are distinct from the TMs found in the other two types of muscle (Heeley and Hong, 1994;Heeley et al, 1995).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additional isoforms of either Tm or TnT may be revealed with two-dimensional gel electrophoresis (e.g. Heeley et al, 1995). Undetected species-related differences in post-translational modifications (e.g.…”
Section: Discussionmentioning
confidence: 99%